Micro and Nano Influencers: Bibliometric Mapping of Influencer Marketing Trends - Judijanto, Loso; Endarwati, Esti Tri; Tiofanny, Claudie; Moktar, Brilian; Harja, Ngiw Aman (West Science Social and Humanities Studies, 2025)
This study conducts a bibliometric analysis of the research on micro and nano influencers within the broader field of influencer marketing. Using VOSviewer for bibliometric mapping, the study identifies key themes, trends, and influential contributors to the literature. The analysis reveals that influencer marketing, particularly in the context of micro and nano influencers, has evolved significantly, with increased focus on consumer behavior, purchase intention, and authenticity. The study highlights the centrality of platforms such as Instagram and TikTok in influencer marketing research, while also emphasizing the growing integration of influencer-driven strategies with e-commerce and social commerce. Key authors such as De Veirman, Hudders, and Schouten have shaped the intellectual structure of the field. This research provides valuable insights into the development of influencer marketing and suggests future directions for exploring platform-specific strategies, ethical considerations, and the global impact on diverse consumer segments.